2022
DOI: 10.1186/s12879-022-07538-5
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term mortality in patients with urosepsis caused by Escherichia coli susceptible and resistant to 3rd generation cephalosporins

Abstract: Background The aim of this study was to compare short- and long-term mortality among patients with urosepsis caused by Escherichia coli susceptibile (EC-SC) and resistant (EC-RC) to 3rd generation cephalosporins. Methods A retrospective cohort study that included all patients with E. coli urosepsis admitted to a 700-bed hospital from January 2014 until December 2019. Mortality up to 30 days, 6 months and 1 year was assessed using logistic multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Tocut et al in a retrospective cohort of urosepsis have shown mortality of 6.3% -12.7% in sensitive and resistant E.coli strain respectively. 14 Another retrospective study done by Tal et al in elderly patients with bacteremic UTI found in hospital mortality of 33%. 15 There is scarce data to the best of our knowledge on head to head comparison of bacteremic versus non bacteremic UTI in terms of mortality.…”
Section: Resultsmentioning
confidence: 98%
“…Tocut et al in a retrospective cohort of urosepsis have shown mortality of 6.3% -12.7% in sensitive and resistant E.coli strain respectively. 14 Another retrospective study done by Tal et al in elderly patients with bacteremic UTI found in hospital mortality of 33%. 15 There is scarce data to the best of our knowledge on head to head comparison of bacteremic versus non bacteremic UTI in terms of mortality.…”
Section: Resultsmentioning
confidence: 98%
“…In-hospital mortality for sepsis from urinary focus has been described as 40% in a large multicentric retrospective study carried out from 2004 to 2018 in the USA [ 66 ], which included patients from the ICU, medical wards, nursing homes, and outpatients, which could explain why it is higher than the results in this study, 17.6% and 23.3% for in-hospital and 30-day mortality, respectively. Tocut et al [ 67 ] described a 30-day mortality of 8.6% in their retrospective cohort; however, their diagnosis of urinary sepsis was only based on clinical criteria and their patients were younger. Holmbom et al [ 31 ] described a 30-day mortality of 14% in a retrospective analysis of an open urologic cohort in Sweden; however, diagnosis of sepsis was clinical (ICD-10 codes), the mean age of the cohort was a decade younger than the mean age in this study, and the mean Charlson Comorbidity Index was 2.2, while in this study 95.3% of the patients had a Charlson Comorbidity index of ≥3.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors have been identified: diabetes mellitus, length of hospitalization, Klebsiella spp infection and the presence of an indwelling urinary catheter [ 38 ]. Additionally, the rate of mortality was thoroughly evaluated at 1, 2, 6 and 12 months and the trend steadily increased from 8.6% in the first month to 17.6% in a year [ 39 ]. Factors that predicted mortality at 30 days were Charlson score and infection with a strain of E. coli with resistance to 3rd generation cephalosporins [ 39 ].…”
Section: The Role and The Characteristics Of The Urinary Microbiome P...mentioning
confidence: 99%
“…Additionally, the rate of mortality was thoroughly evaluated at 1, 2, 6 and 12 months and the trend steadily increased from 8.6% in the first month to 17.6% in a year [ 39 ]. Factors that predicted mortality at 30 days were Charlson score and infection with a strain of E. coli with resistance to 3rd generation cephalosporins [ 39 ]. In addition, it should be kept in mind that not only this severe complication is to be avoided, but, ideally, even uncomplicated UTIs, as studies claim increased risk for renal events and an accelerated progression of CKD in patients in stages G3-G5 with UTI [ 3 , 6 , 9 ].…”
Section: The Role and The Characteristics Of The Urinary Microbiome P...mentioning
confidence: 99%